Modeling Surface Recombination at the p-Type Si/SiO2Interface via Dangling Bond Amphoteric Centers - Moustafa Y. Ghannam; Husain A. Kamal (Advances in Condensed Matter Physics)
An integral model is proposed for recombination at the silicon/silicon dioxide (Si/SiO2) interface of thermally oxidized p-type silicon via Pb amphoteric centers associated with surface dangling bonds. The proposed model is a surface adaptation of a model developed for bulk recombination in amorphous silicon based on Sah-Shockley statistics which is more appropriate for amphoteric center recombination than classical Shockley-Read-Hall statistics. It is found that the surface recombination via amphoteric centers having capture cross-sections larger for charged centers than for neutral centers is distinguished from Shockley-Read-Hall recombination by exhibiting two peaks rather than one peak when plotted versus surface potential. Expressions are derived for the surface potentials at which the peaks occur. Such a finding provides a firm and plausible interpretation for the double peak surface recombination current measured in gated diodes or gated transistors. Successful fitting is possible between the results of the model and reported experimental curves showing two peaks for surface recombination velocity versus surface potential. On the other hand, if charged and neutral center capture cross-sections are equal or close to equal, surface recombination via amphoteric centers follows the same trend as Shockley-Read-Hall recombination and both models lead to comparable surface recombination velocities.